2019
DOI: 10.1002/jhbp.700
|View full text |Cite
|
Sign up to set email alerts
|

Reticular pattern around superior mesenteric artery in computed tomography imaging predicting poor prognosis of pancreatic head cancer

Abstract: BackgroundSome patients with pancreatic ductal adenocarcinoma (PDAC) demonstrate a reticular pattern around the superior mesenteric artery (SMA) in computed tomography scans. This study aimed to clarify the clinical significance of the reticular pattern in pancreatic head cancer.MethodsA total of 91 patients with pancreatic head cancer, who underwent upfront pancreaticoduodenectomy between 2004 and 2017, were included. Patients without reticular pattern (Non‐group, n = 39); with reticular pattern around SMA (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In previous studies, this phenomenon was described as cancer-infiltration-mimicking fibrous adhesion or an inflammatory reaction [5,10,11]. Kato et al found impaired overall survival rates and a higher rate of early distant metastasis in patients with a reticular pattern surrounding the SMA [19]. We recently demonstrated that perivascular SMA stranding is a preoperative radiological marker of fibrotic stroma resection (S+ status) at the mesopancreatic resection margin [20].…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies, this phenomenon was described as cancer-infiltration-mimicking fibrous adhesion or an inflammatory reaction [5,10,11]. Kato et al found impaired overall survival rates and a higher rate of early distant metastasis in patients with a reticular pattern surrounding the SMA [19]. We recently demonstrated that perivascular SMA stranding is a preoperative radiological marker of fibrotic stroma resection (S+ status) at the mesopancreatic resection margin [20].…”
Section: Discussionmentioning
confidence: 88%
“…Kim et al 28 analyzed 139 RPDAC patients who underwent upfront surgery and found that MST in patients with CA 19‐9 level <93 and ≥93 U/mL were 28 and 21 months, respectively. Regarding conditional factors of RPDAC, Kato et al 37 retrospectively reviewed 157 RPDAC patients who underwent upfront surgery and reported that MST of the overall cohort was 40 months; PS ≥2 (HR 2.47, P = .014) and lymph node metastasis suspected by imaging (HR 1.55, P = .003) were significant independent predictors of poor prognosis. Kawai et al 29 retrospectively analyzed 102 patients with resectable body/tail PDAC and found that MST among resectable, resectable with SV (splenic vein) invasion, and resectable with SA (splenic artery) invasion was 80.6, 23.4, and 15.1 months, respectively, suggesting that SA invasion is a notably unfavorable prognostic factor.…”
Section: Resectability Criteria and Corresponding Optimal Treatment S...mentioning
confidence: 99%